THE PERCEPTION OF SUPPLY CHAIN ACTORS ON FACTORS THAT DETERMINE FRESH TOMATO SUPPLY IN BAUCHI STATE, NIGERIA - Atman, F. M.; Yakubu, S.; Bala, A. H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to examine the determinants of fresh tomato supply in Bauchi State, Nigeria. A multistage sampling technique was used to select 301 producers, 105 wholesalers, 252 retailers and 150 consumer making a total of 808 Supply Chain Actors (SCA) for the study. Data were collected using structured questionnaire and analysed using descriptive statistics. The result reveals that 76.7%, 78.2%, 76.5% and 78.6% of the producers, wholesalers, retailers and consumers to be between the age category of 21-50 years old. Further, the result shows a mean age of 40 years old for the SCA in all the zones. The result reveals that consumers in all the zones agree that all the stated factors were determinants of fresh tomato supply (mean = 3.07 to 4.95). However, they disagree on packaging, and organic products as a determinants of fresh tomato supply. Price of tomato, seasonality and sorted tomato mean = 2.58, 1.23 and 2.93 respectively, were not considered as determinants by the wholesalers. All factors stated were regarded as determinants of supply by the retailers. While consumers disagree with packaging ( mean = 1.67) and organic (mean = 1.67) as determinants of supply. It is concluded that all the SCA in Bauchi State agree and disagree on some factors as the determinants of fresh tomato supply. Therefore, the study recommends that Supply chain actors particularly producers and marketers of fresh tomato should look into the factors considered by the consumers as obstacles to the supply of tomato and improve on them so as to increase its consumption and in return increase their profit. Also, using the appropriate technologies, producers should be able to produce tomato with desired qualities that will attract consumers.